Perspektif nabawi melalui pendekatan sabar dalam institusi kekeluargaan - Mohammad Haafiz Aminuddin Mohd Azmi; Abu Dzar Ahmad; Ahmad Haiqal Fitri Ahmad Fuad; Muhamad Razif Ahmad; Mohd Arif Nazri (Universiti Sains Islam Malaysia, 2025)
‘Abqari Journal. Volume 31 Issue 1 (Oct. 2024) Page (1–17)